AKIBAT HUKUM RANCANGAN UNDANG-UNDANG YANG DISETUJUI BERSAMA DPR DAN PRESIDEN TETAPI TIDAK DITANDATANGANI PRESIDEN - Amar Ridhwan Pangestu, (2022)
Provisions relating to the formation of laws and regulations are contained in Law Number 12 of 2011 concerning the Establishment of Legislations. To create a regulation in the form of a law in Indonesia, Article 20 paragraph 2 of the 1945 Constitution states that "Every draft law is discussed by the House of Representatives and the President for mutual approval". The problem that arises is how the location of a law can be said to have binding power, and also whether a law that is not signed by the President can be said to have no mutual agreement. The result of the research based on this problem is that the binding power of a statutory regulation appears when the regulation has been promulgated because the promulgation of the regulation is a form of recognition of sovereignty by the people themselves. Then from the second problem, the power to make laws is in the hands of the DPR, but the DPR cannot run alone without the president's approval in making laws. No draft law becomes law if one of the DPR or the President does not approve of the bill. Therefore, there must be an agreement between the parties in the process of discussing the draft law.